Hubungan Penggunaan Media Sosial dengan Kulitas Tidur pada Siswa di MTS Yapina Kota Depok - Ruswandi, Umar; Fitriyani, Lia (Universitas Malahayati, 2023)
ABSTRACT The duration of social media use in Indonesia is ranked 9th globally, namely 2.9 hours per day. Social media users love various kinds of social media platforms. The WhatsApp platform is 88.8%, Instagram is 84.8%, and Facebook is 81.3%, occupying the position of the most interested among other platforms. The relationship between the use of social media and the quality of sleep of students at MTS Yapina, Depok City, is known. The research method used is descriptive analytic research, the research design uses cross sectional. The population in this study were all students at MTS Yapina Depok City as many as 92 students. The sample in this study were 92 students. The sampling technique used in this research is total sampling. Data collection techniques were carried out by interviewing respondents using a questionnaire. Data analysis was performed using statistical tests in the form of univariate tests and bivariate tests with chi-square analysis. Duration of social media use > 2 hours per day and poor sleep quality by 35.9% (33 students). The results of the chi square test showed that there was a relationship between the duration of social media use and the sleep quality of students at MTS Yapina, Depok City (p value = 0.018). There is a relationship between the duration of social media use and the sleep quality of students at MTS Yapina, Depok City Keywords: Social Media, Sleep Quality, Students ABSTRAK Durasi penggunaan media sosial di Indonesia menempati ranking ke-9 secara global yaitu 2,9 jam per hari. Pengguna media sosial menggemari berbagai macam platform media sosial. Platform WhatsApp sebesar 88,8%, Instagram sebesar 84,8%, dan Facebook sebesar 81,3% menempati posisi peminat terbanyak diantara platform lainnya. Diketahuinya hubungan penggunaan media sosial dengan kualitas tidur pada siswa di MTS Yapina Kota Depok. Metode penelitian yang digunakan penelitian adalah analitik deskriptif , desain penelitian menggunakan yaitu cross sectional. Populasi dalam penelitian ini adalah seluruh siswa di MTS Yapina Kota Depok sebanyak 92 siswa. Sampel dalam penelitian ini sebanyak 92 siswa. Teknik sampling yang digunakan dalam penelitian ini adalah total sampling. Teknik pengumpulan data dilakukan dengan cara wawancara pada responden menggunakan kuesioner. Analisis data dilakukan dengan uji statistik yang berupa uji univariat dan uji bivariat dengan analisis chi-square. Durasi penggunaan media sosial > 2 jam perhari dan kualitas tidur buruk sebesar 35,9% (33 siswa). Hasil uji chi square didapatkan hasil bahwa terdapat hubungan durasi penggunaan media sosial terhadap kualitas tidur pada siswa di MTS Yapina Kota Depok (p value = 0,018). Terdapat hubungan durasi penggunaan media sosial terhadap kualitas tidur pada siswa di MTS Yapina Kota Depok Kata Kunci: Media Sosial, Kualitas Tidur, Siswa